A council for the global church : receiving Vatican II in history - Faggioli, Massimo (Fortress Press, 2015)
The year 2015 marks the fiftieth anniversary of the close of the Second Vatican Council. In light of recent developments--especially the resignation of Benedict XVI, the election of Pope Francis, and the Bishops' Synods of October 2014 and 2015--this volume provides an analysis of Vatican II, the most decisive and far-reaching event in the modern Catholic Church. Explicating pivotal elements of the Council, its decision-making process and the deep consequences of its final decisions, Massimo Faggioli contributes an accessible presentation of the significance of Vatican II for the church and its life in the modern world beyond the boundaries of the Roman Catholic Church. As the Council, since its conclusion, has been subjected to various interpretations--a matter of not little controversy--the volume explores the contours of subsequent interpretation and variations in approach, especially those that have marked the eras of John Paul II and Benedict XVI. Despite these controversies, however, the Council lives on, the author argues, in theology, especially the ad intra and ad extra dimensions of reform in the liturgy, the church and the modern world, and religious freedom, continuing to have global impact on Catholics and non-Catholics.